2014
DOI: 10.1177/0954405413514745
|View full text |Cite
|
Sign up to set email alerts
|

Experimental modelling and multi-response optimization of travelling wire electrochemical spark machining of Pyrex glass

Abstract: The present study focuses on experimental modelling of travelling wire electrochemical spark machining process using coupled methodology comprising Taguchi methodology and response surface methodology. Experiments were conducted on Pyrex glass workpiece using L27 orthogonal array considering applied voltage, pulse on-time, pulse off-time, electrolyte concentration and wire feed velocity as input parameters and material removal rate, surface roughness (Ra) and kerf width (Kw) as output parameters. The multi-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The increase in machining voltage stepped up hydrogen bubbles generation rate which played a significant role in sparking intensity of ECDM process. 124 However, the effect of machining voltage on MRR is limited up to a certain value. The authors revealed 61 the decrease in MRR at 100 V due to limited flushing of debris in machining zone.…”
Section: Machining Qualitymentioning
confidence: 99%
“…The increase in machining voltage stepped up hydrogen bubbles generation rate which played a significant role in sparking intensity of ECDM process. 124 However, the effect of machining voltage on MRR is limited up to a certain value. The authors revealed 61 the decrease in MRR at 100 V due to limited flushing of debris in machining zone.…”
Section: Machining Qualitymentioning
confidence: 99%
“…In present study, the surface roughness has been taken as response parameter. Therefore, the "lower is better" quality characteristic has been used to analyze the experimental results, which can be determined as [19,20]:…”
Section: Experimantationmentioning
confidence: 99%
“…GA is a stochastic search algorithm that is effective and has been applied very widely to get the global optimal value. 1822 A BiGA developed to deal with the static mathematical model. The algorithm has two genetic optimization processes at different levels where the lower level GA is embedded in the higher level one.…”
Section: Bigamentioning
confidence: 99%